Clinical Case of Rare Genetic Disorder (Proud Syndrome) in a Child - Anastasiia N. Vertianova; Anna V. Monakhova; Ulyana S. Suraeva; Olga M. Matiasova; Alla Yu. Shutkova; Elena V. Tush; Elena E. Yacishina; Marina A. Suslova; Olga V. Khaletskaya (Педиатрическая фармакология)
Background. Proud syndrome is rare inherited disease with X-linked inheritance associated with mutations in the homeobox gene ARX. Typical clinical signs of this syndrome are severe mental retardation, intractable epilepsy, agenesis (dysgenesis) of corpus callosum. Less common features are genital abnormalities, microcephaly, facial dysmorphia, and skeletal malformations. Clinical case description. The article describes the clinical findings of Proud syndrome in girl A., admitted to Children’s City Clinical Hospital No. 1 in Nizhny Novgorod. The girl was born without asphyxia at term through natural vaginal delivery after the first uneventful pregnancy. Body weight at birth was 2600 g. The genealogical history is burdened by the presence of epilepsy in girl’s father relatives. There were no deviations in psychomotor skills development before disease onset. Hemi-convulsive seizures (switching sides) have appeared at the age of 6 months. These attacks had status course and were resistant to anticonvulsant therapy. Neuroimaging has revealed agenesis of corpus callosum. Regression of psychomotor development, new behavioral disorders (stereotypes and auto-aggression), hyperexcitability, and sleep disorders were observed in dynamics. The diagnosis of Proud syndrome was confirmed by identification of probably pathogenic mutation in the ARX gene (c.1111C>T, p. Arg 371*64). The features of anticonvulsant management were demonstrated in the patient. Conclusion. This clinical case presents typical clinical picture of Proud syndrome. The disease is non-curable. Such patients should be administered with syndromic therapy: constant anticonvulsant therapy, correction of behavioral disorders (classes with specialist on mental defects), neurologist, epileptologist, psychiatrist observations. Parental examination is crucial ARX mutation search in order to determine the prognosis for further child-bearing (parents refused to perform genetic study at the time of article writing).